The Effect of Debt Policy on Financial Performance in Automotive Sub-Sector Companies Listed on the Indonesia Stock Exchange - Nabila, Puput; Alwi, Alwi; Herman, Herman (Journal of Economics, Management and Accounting (JEMA), 2024)
This study uses three indicators, namely the short-term debt ratio and the long-term debt ratio, to see the effect on profitability measured using return on equity. This study uses a sample of this research is the sub-sector of automotive companies listed on the Indonesia Stock Exchange (IDX) in 2013 - 2022. The observable sample was 5 samples that met the criteria for ten years of research. The sampling method used is purposive sampling. The data analysis method used is multiple linear regression analysis. The results of this study show that short-term debt variables have a negative and significant effect on profitability, this can be seen with a level of significance with a value of 0.034 < 0.05. The long-term debt variable has a negative and insignificant effect on profitability, this is also seen with a level of significance with a value of 0.007 < 0.05.